2020
DOI: 10.1111/bju.15135
|View full text |Cite
|
Sign up to set email alerts
|

68Ga‐PSMA‐PET/CT helps to select patients for salvage radical prostatectomy with local recurrence after primary radiotherapy for prostate cancer

Abstract: Objective To investigate the diagnostic performance of gallium‐68 prostate‐specific membrane antigen positron emission tomography/computed tomography (68Ga‐PSMA PET/CT) in patients with recurrent prostate cancer with regard to the presence of lymph node metastases (LNM) and local recurrences after primary radiotherapy. Patients and methods We retrospectively reviewed 142 patients following salvage radical prostatectomy (sRP), 50 of which had a 68Ga‐PSMA PET/CT performed as a preoperative staging module. Predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
(35 reference statements)
1
22
0
Order By: Relevance
“…Dinis Fernandes et al showed that in 5/21 patients with radio-recurrence, radiologist contours on mpMRI did not visually overlap with step-section pathology [10]. Similarly, for PSMA-targeted PET/CT, Pfister et al reported per-lobe sensitivity and NPV of 81% and 32% respectively based on salvage prostatectomy in patients previously treated with RT or HIFU [26]. In our study, even with combined PET/CT and mpMRI, the false negative rate per-lobe was 11%.…”
Section: Discussionmentioning
confidence: 98%
“…Dinis Fernandes et al showed that in 5/21 patients with radio-recurrence, radiologist contours on mpMRI did not visually overlap with step-section pathology [10]. Similarly, for PSMA-targeted PET/CT, Pfister et al reported per-lobe sensitivity and NPV of 81% and 32% respectively based on salvage prostatectomy in patients previously treated with RT or HIFU [26]. In our study, even with combined PET/CT and mpMRI, the false negative rate per-lobe was 11%.…”
Section: Discussionmentioning
confidence: 98%
“… 31 , 32 , 33 Indeed, several studies have demonstrated the superiority of PSMA PET/CT over conventional imaging in staging patients with radiation recurrent PCa. 34 , 35 Despite these limitations, we were able to present the first study to comprehensively analyze the role of lymph node yield and the number of positive lymph nodes in patients with radiation recurrent PCa treated with SRP.…”
Section: Discussionmentioning
confidence: 99%
“…Especially due to the advent of prostate-specific membrane antigen (PSMA) positron emission tomography (PET) before SRP, very important details on disease burden are unmasked and should be an integral part of the staging routine in this setting. 13,14 In this regard, PSMA PET helps in the clinical decision-making process and eventually may decrease overtreatment rates in patients who already present with nodal or distant metastasis. Indeed, as evidenced by previous analyses, the presence of positive lymph nodes is a significant contributor to worse oncological outcomes including biochemical recurrence, metastatic progression, and ultimately also cancer-specific mortality.…”
Section: Discussionmentioning
confidence: 99%